Analysis Using R Software: A Big Opportunity for Epidemiology and Public Health Data Analysis - Rinaldi Daswito; Besral Besral; Radian Ilmaskal (RRZ Scientific Publishing, 2023)
R is a programming language, open-source, developed by various of the world's most active statisticians with powerful function and visualization for data analysis from simple to complex data such as machine learning and artificial intelligence. Data visualization technologies have the ability to assist public health professionals with decision-making. Visualization appears to help decision making by increasing the quantity of information communicated and reducing the cognitive and intellectual strain of processing information. There are numerous commercially available statistical software packages that are widely utilized by epidemiologists worldwide. For industrialized nations, the price of software is not a significant issue. However, for underdeveloped nations, the true expenses are frequently excessive. Some academics in developing nations rely on software that has been illegally copied a copy of the software program. There are several benefits to using R, including the possibility of using software packages for free (open source) and the volume and availability of software packages. It is simple to retain and repeat commands on the same data analysis with multiple data frames, facilitating the work of health monitoring officers who frequently analyze data with similar variables but at different times.